Punishment through Forgiveness in Workplace: Rediscovering Kiekegaard’s Knight of Faith in the Abraham Story on Punishment and Forgiveness - ugo CHUKS okolie (Indonesian Journal Of Business And Economics, 2023)
Punishment through forgiving is a useful conflict resolution technique that has many advantages in the workplace (for example, for team dynamics, staff members, organizations and dyadic relationships). However, significant conceptual issues have come to light, particularly as academics have started to look at forgiveness in the workplace. This study therefore focuses on punishment and forgiveness that staff members frequently use to overcome their unfavorable reactive attitudes. We conduct a critical review and analysis of the existing literature to identify key conceptual issues that are posing problems for the study of punishment through forgiveness in organizational behavior in order to better understand these problems. According to this study, only a punisher with the personal minds of a Knight of Faith could successfully implement an effective punitive process at work. The story of Abraham served as an example of how God, a Knight of Faith, repaired his relationship with Abraham through punishment and forgiveness. At the individual level, this procedure is comparable to the one used by Nelson Mandela in the South African. The Sarbanes-Oxley Act, passed in response to the Enron and WorldCom scandals, is used as an example of how traditional retributive approaches can be more ineffective in achieving reconciliation and reestablishing effective relationships. This study offers fresh, practical understandings of how to facilitate and effectively manage punishment through forgiveness in the workplace. Based on these observations, we concluded that unfavorable reactive attitudes can dominate a staff member's thoughts and keep them from having positive attitudes and feelings at work. As a result, employees frequently look for ways to effectively and productively get rid of their negative reactive attitudes.